Effect of neem (Azadirachta indica), girawa (Vernonia amygdalina) leaves meal and garlic (Allium sativum) on performance and egg qualities of layer chickens - Minichle Yigrem; Getachew Animut; Yeshambel Mekuriaw (Journal of Applied Poultry Research)
SUMMARY: A study was conducted to evaluate the efficacy of neem, girawa leaves meal, and garlic for layer hens on performances and egg quality parameters. A total of 128 bovans brown layer hens with uniform body weight (BW) were randomly distributed to 4 treatments, each with 4 replications in a completely randomized design (CRD). The treatments consisted of a commercial diet without additives (T1), and the remaining groups received commercial diet with neem leaf meal (T2), girawa leaf meal (T3), and garlic powder (T4) at 2.5% level of inclusion. Performance parameters such as hen-day egg production, egg weight, feed intake, and internal and external egg qualities were evaluated for the laying hens. The results showed that the highest feed intake was reported in T2 (117.77 g/hen) and T4 (117.12 g/hen), while the lowest was reported in T3 (108.20 g/hen) compared to T1 (110.51 g/hen). Neem had the highest (P < 0.05) hen-day egg production (92.45%), followed by garlic (89.78%), and the least hen-day egg production was recorded in girawa (83.86%) compared to control (87.4%). The egg mass was highest for T2, while T1 and T3 had the lowest. No significant difference was observed in egg weight, shell thickness, shell weight, albumin height, albumin weight, yolk weight, yolk height, and yolk diameter. However, egg length and yolk color were significantly (P < 0.05) higher in T2. Therefore, it was concluded that neem leaf meal can be recommended in this study, and it has a good phytogenic feed additive for layer performance and egg qualities.